Enhancing the Pedagogical Competence of ECE Teachers through the Creation of Comprehensive Game Tools - Sri Tatminingsih; Budi Hermaini; Mutiara Magta (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The ability of Early Childhood Education (ECE) teachers to create instructional materials constitutes one of their pedagogical competencies. This competence entails overseeing the development process, which consists of planning, executing, and evaluating the development process and its outcomes. This article aims to describe the procedure involved in the conception and development of comprehensive game tools (CGT) to enhance the pedagogical competence of ECE teachers. This community service instructs and equips teachers in developing CGTs, conducted in a blended method within six weeks. Specifics of offline materials consist of the following: 1) activity schedule, 2) understanding of the nature of CGTs, 3) product development, 4) revision of results, and 5) product evaluation. Online resources provide instruction on 1) developing and creating designs and 2) constructing comprehensive game tools. Thirty teachers from PAUD Katuk and Asyifa Islamic Kindergarten - South Jakarta were participants. The final product is comprised of 5 CGTs, and the teachers' ability to design and develop CGT is enhanced. Suggestion: CGT development should be conducted under intensive supervision.